Non-pecuniary loss in commercial contracts with special emphasis on the United Nations Convention on Contracts for the International Sale of Goods (CISG) - Dupont, Alain (Department of Private Law, 2026)
How should we deal with situations where non-pecuniary loss is caused by a breach of contract? While non-pecuniary loss is often discussed and broadly accepted in the field of tort law, it has remained rather unnoticed in writings concerned with contract law. The question shall be examined in this thesis with regard to different countries and with particular emphasis on the United Nations Convention on Contracts for the International Sale of Goods.1 The perspective on this issue is a personal one; one of a lawyer coming from a civil law system familiar with Swiss terminology.2 A comparative approach of damages implicates several difficulties. First of all, there is no commonly accepted definition of damage. As a principle, damage can be recovered only if the loss or harm occurred is damage in the eyes of the law.3 One can therefore only ask if non-pecuniary loss is acknowledged by a certain system rather than generally. Furthermore, the issue of limiting damages is an integral part of any legal regulation of damages. Certainty and predictability in the rules on damages is achieved on the theoretical basis for regulation of the mechanism of limiting damages.